Complicated corneal ulcer and its treatment in a horse - Kilic, S; Unsaldi, S (Indian Veterinary Journal, 2005)
Corneal ulcer is one of the most common ocular diseases threatening vision in horse (Gelatt, 1991). It can either result from ocular trauma (McLauglin et al., 1985) infections (Sweeney and Irby, 1996) or secondary to other ocular diseases (McLellan and Archer, 2002). Since the cornea is the most powerful refractive surface of the eye, maintaining its state of transparency is essential during treatment (Gelatt, loc. cit.). Successful therapy of corneal ulcer can be achieved provided the diagnosis is made early and the treatment is specific (Nasisse and Nelms, 1992). Subpalpebral lavage system (SLS) of medication has, been indicated in, nervous horses and those requiring topical therapy at frequent intervals (Gelatt, loc. cit.). In this study, a complicated traumatic corneal ulcer and its response to topical medication via SLS in a horse is described.